Identifying uniform corrosion of carbon steel using electrochemical noise measurement / Shirley Arvilla Andrew, Khaidzir Hamzah and Tammie Christy Saibin - Andrew, Shirley Arvilla; Hamzah, Khaidzir; Saibin, Tammie Christy (Universiti Teknologi MARA, Sabah, 2017)
In this study, the electrochemical noise (ECN) measurement technique was utilized to identify the uniform corrosion of carbon steels in the solutions of hydrochloric (HCl), sulphuric (H2SO4), sodium chloride (NaCl), sodium hydroxide (NaOH), potassium hydroxide (KOH) and calcium hydroxide (Ca(OH)2). ECN is the fluctuations of current and potential of a corroding system. The potential of electrochemical noise was measured between a working electrode and a reference electrode whereas the current of electrochemical noise was measured between two working electrodes in an electrochemical cell. The data from the measurements were statistically analyzed using time and frequency domains. The time domain analysis reveals the characteristics of a particular corrosion type. The frequency domain analysis estimates the power spectra at various frequencies and the statistical analysis calculates electrochemical noise parameters such as the mean, standard deviation, noise resistance (RN), coefficient of variation (CoV), characteristic charge (q) and corrosion current (Icorr). The results of the time domain analysis show that uniform corrosion only occurred in acidic solutions of HCl and H2SO4. The frequency domain analysis was found to be an unsuitable method to identify uniform corrosion in the corrosion system used. The statistical analysis shows that the corrosion rate was greater when using the solutions of HCl and H2SO4 compared to NaCl, NaOH, KOH and Ca (OH)2.